Analisis Rima dalam Tembang di Bengkulu Selatan - Rahmadani, Septi; Zasrianita, Fera; Heriadi, Meddyan (Jurnal Kajian Ilmu Pendidikan (JKIP), 2024)
Local culture such as tembang is starting to disappear where the younger generation tends to prefer foreign culture, thereby making local culture marginalized, tembang is generally better understood by the older generation than the younger generation. The aim to be achieved in this research is to describe, analyze and conclude the rhymes contained in songs in South Bengkulu. This research uses qualitative research. The data source was obtained from primary data. The primary data source came from observations via five YouTube videos on the Wengki Studio channel and secondary data was obtained from document studies which included various sources such as books, journals and theses related to songs in South Bengkulu. The results of this research are that from the first song video there are two perfect rhymes, three front rhymes, two end rhymes, two chain rhymes and sixteen paired rhymes or twin rhymes. From the second song video there are four end rhymes and six broken rhymes from the third song video. There are five cross rhymes from the fourth song video, there are four cross rhymes and from the fifth song video there are two twin rhymes, two end rhymes, two continuous rhymes or chain rhymes and four paired or twin rhymes. Of the five song videos there are five Twenty-four rhymes in the song video in South Bengkulu on the YouTube video channel Wengki Studio. The rhymes that are most often found in this song are twenty-two rhymes in pairs or twin rhymes, while the rhymes that are least found are chain rhymes of two rhymes.